Warfare in late neolithic\early chalcolithic Pisidia, southwestern Turkey - Clare, Lee (Documenta Praehistorica, 2008)
This paper proposes an association between climate forcing connected with the 8200 calBP "climate event" and a postulated phase of internecine warfare and population collapse at Late Neolithic/Early Chalcolithic sites in Pisidia, southwestern Turkey. A summary of this evidence is provided and a hypothetical scenario considered in the context of contemporaneous developmentsin neighbouring regions.
Keywords: archaeology; arheologija; neolitik; paleoklimatologija; klimatske spremembe; demografski razvoj; zgodovinska demografija